Economic aspects for evaluation of logistic systems - Tsanev, Tsanko (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The economic aspects of evaluation of logistic systems are presented in the paper and factors for differentiated evaluation of the financial state, purchasing power, the population with its number and ethnicity and specific preferences, the mass consumption in the region, the trade in the country and abroad, variety, quality and the corresponding competitive price.